TINGKAT KOMUNIKASI SOSIAL MASYARAKAT DI LINGKUNGAN GANG PERTIWI BARU, KELURAHAN BANTAN, KECAMATAN MEDAN TEMBUNG, KOTA MEDAN - Fauzi Kurniawan; Anifah; Debby Triposa Kaban; Ismayani Chairunnisa; Saulina Ulfah Dalimunthe; Rahma Avisya Tifara; Yonathan Steve Legie; Khairunnisa; Miftahul Jannah; Maydina Iswatun; Naufal Dzakhwan Bayhaq (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the level of social communication among residents in the Gang Pertiwi Baru neighborhood, Bantan Village, Medan Tembung Subdistrict, Medan City. The method used was quantitative research with a descriptive approach. The study population consisted of 59 people, with a sample of 34 respondents selected using purposive sampling. Data collection was conducted via a questionnaire using a Likert scale consisting of 20 statements. The data were analyzed using mean calculations. The results of the study indicate that the mean score for social communication was 4.36, which falls into the “very good” category. The indicator of community cooperation received the highest score, while the indicators of information dissemination and community participation were still relatively lower. This indicates that social communication has been effective; however, improvements are still needed in the equitable distribution of information and community involvement so that social communication can function more optimally.